PEMBUATAN GAME EDUKATIF MENGGUNAKAN APP INVENTOR DENGAN TEMA MATA PELAJARAN KIMIA - Rizky Parlika; Olivia i Anggun Permatasar; Rifardi Taufiq Yufananda; Dimas Rizward Hikmah Utomo; Mochammad Zayyan Ramadhan; Isfan Rachmad (Universitas Narotama, 2018)
Abstract : The problem in this research is to make a suitable learning media applied to high school students as an independent media and interkative, So that the application of learning model used by the teacher is not boring tend to be fun and can improve learning outcomes. The objectives of the researcher to accomplish is to develop and produce android application products in the form of educational media learning games about Chemistry, and know the feasibility and effectiveness of educational game applications as learning media for student study supplement with Chemical material. This research method using Research and Development method with design / design is pre-experimental design with one-group pretest-posttest design. The results that have been obtained is to produce application products android educational game Chemistry. It can be concluded educational game media application of Chemistry learning and effective as learning media for student study supplement. Keywords-App Inventor, Chemistry, Android